Updates on Management of Avascular Necrosis Using Hip Arthroscopy for Core Decompression - Kunze, Kyle N.; Sullivan, Spencer W.; Nwachukwu, Benedict U. (Frontiers in Surgery, 2022)
Osteonecrosis of the femoral head (ONFH) is caused when circulation within the femoral head is disrupted. Etiology of this disease is characterized by either traumatic events or atraumatic risk factors, such as chronic alcohol consumption or glucocorticoid use. ONFH commonly presents as pain in the groin, gluteus muscles, and/or knee with reductions in internal rotation range of motion of the hip. ONFH pathology can be confirmed with radiographic or advanced imaging and characterized by stage, size and location of the lesion. Treatment for ONFH consists of conservative and therapeutic methods as well as surgical intervention. Historically, ONFH has been treated using total hip arthroplasty (THA), but with increasing incidence in a younger, active population, measures to preserve the native hip joint have been explored. Recent advancements in hip arthroscopy and arthroscopy-assisted core decompression have led to improved outcomes, reduced pain and higher hip survival rate for early onset ONFH compared with more invasive approaches such as THA. Biologic treatments combined with arthroscopic core decompression have also shown improved outcomes and quality of life in few reports, suggesting a potential role for biologic adjuncts. The current study provides a comprehensive review and update on the literature surrounding arthroscopy-assisted core decompression for patients with ONFH.